Latihan Kepemimpinan Dasar bagi Siswa Madrasah Aliyah - Luwihta, Aisyah Dana; Ilmiya, Inayatul (PT. Cahya Edupreneur Indonesia, 2023)
Just as the era continues to develop, so does leadership which scientifically will continue to develop following the development of scientific management which continues to grow which we can identify with the science of leadership. We can see this from various sources of studies on leadership with various perspectives and of course various perspectives. It is not enough for us to pay attention to the good results of leadership alone, but we need to pay attention to preparing a discourse in an orderly manner so that we can train future leaders. We as educators need to pay special attention to our students, especially as candidates for the future leaders of our nation and state. In this case, we can introduce students from now on to various kinds of theories and skills about leadership, so that students are able to become leaders for themselves or leaders in a group of people or an organization. Becoming a leader is certainly not an easy thing, there are conditions that need to be met. Because a leader is the spearhead of his group. The community service that we have done is based on the many problems that arise among students that often occur, so that they can damage their future. This community service uses the lecture method, question and answer and indoor outbound. From this community service that we have carried out, it can be found that there is an increased understanding of MA Nurut Taqwa students about how to prepare themselves to become good leaders.